2019
DOI: 10.5812/ijp.90663
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 135 Cases of Pediatric Henoch-Schönlein Purpura in Gansu, Northwestern China

Abstract: Background: Henoch-Schönlein purpura (HSP) is the most widespread systemic small-vessel vasculitis of childhood. Limited information exists about the epidemiology, allergen and laboratory bio-markers reflecting HSP disease phases in Northwestern China. Objectives: To comprehensively evaluate the epidemiology, allergen and laboratory bio-markers reflecting HSP disease phases for the first time in this region. Methods: We retrospectively evaluated 135 HSP patients and 86 controls aged ≤ 14 years admitted to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Over 111 studies were screened and evaluated for inclusion in the current meta-analysis. In our meta-analysis, six studies (26)(27)(28)(29)(30)(31) with 761 participants, were included. Study characteristics (country, study design, GI involvement definition, NOS scale) of the included studies are presented in Table 1.…”
Section: Included Studiesmentioning
confidence: 99%
“…Over 111 studies were screened and evaluated for inclusion in the current meta-analysis. In our meta-analysis, six studies (26)(27)(28)(29)(30)(31) with 761 participants, were included. Study characteristics (country, study design, GI involvement definition, NOS scale) of the included studies are presented in Table 1.…”
Section: Included Studiesmentioning
confidence: 99%
“…Moreover, NLR is inexpensive and easy to assess. Therefore, NLR is useful in evaluating the severity of the disease [ 16 ]. Existing studies have shown that NLR and CRP have higher predictive value for IgAV recurrence in adults [ 17 ]; however, few data are available on similar findings in children.…”
Section: Introductionmentioning
confidence: 99%
“…IgA vasculitis (IgAV) is a common type of vascular inflammation that mainly affects children; however, its cause and pathogenesis remain poorly understood. It also affects adults, but the incidence of the disease is high in children (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) per 100,000 person-years). Although it usually has a favorable prognosis, the recurrence rate is Common laboratory indices, such as C-reactive protein (CRP), procalcitonin, white blood cell (WBC) count, and red blood cell (RBC) count are evaluated to rule out other diseases [8].…”
Section: Introductionmentioning
confidence: 99%